2019
DOI: 10.1186/s12967-019-02157-2
|View full text |Cite
|
Sign up to set email alerts
|

IgA1 deposition may induce NLRP3 expression and macrophage transdifferentiation of podocyte in IgA nephropathy

Abstract: BackgroundThe NLRP3 inflammasome plays an important role in mediating podocyte injury in various kidney diseases. The aim of this study was to investigate whether NLRP3 expression associated with podocyte injury was involved in the pathogenesis of IgA nephropathy (IgAN).MethodsNLRP3 inflammasomes and macrophage marker (F4/80) were detected in the renal tissues of IgAN patients. Association between kidney NLRP3 levels and the clinical feature of IgAN patients was analyzed. Podocytes were incubated with serum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Besides, it is reported that bilirubin interferes with vascular cell adhesion molecule1 (VCAM-1) and intercellular adhesion molecule1 (ICAM-1) to regulate atherosclerotic lesion formation and vascular inflammation both in animal and human models [9,24]. Furthermore, bilirubin participates in immune response at several levels including modulation of regulatory T cells and T helper type 17 (Th17) cells, inhibition of the Toll-like receptor 4/nuclear factor kappaB signaling pathway, down-regulation of NLRP3 inflammasome [8,[24][25][26], which has been proved to be very important for IgA nephropathy in a previous study by our team [27].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is reported that bilirubin interferes with vascular cell adhesion molecule1 (VCAM-1) and intercellular adhesion molecule1 (ICAM-1) to regulate atherosclerotic lesion formation and vascular inflammation both in animal and human models [9,24]. Furthermore, bilirubin participates in immune response at several levels including modulation of regulatory T cells and T helper type 17 (Th17) cells, inhibition of the Toll-like receptor 4/nuclear factor kappaB signaling pathway, down-regulation of NLRP3 inflammasome [8,[24][25][26], which has been proved to be very important for IgA nephropathy in a previous study by our team [27].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is reported that bilirubin interferes with vascular cell adhesion molecule1 (VCAM-1) and intercellular adhesion molecule1 (ICAM-1) to regulate atherosclerotic lesion formation and vascular in ammation both in animal and human models [9,24]. Furthermore, bilirubin participates in immune response at several levels including modulation of regulatory T cells and T helper type 17 (Th17) cells, inhibition of the Toll-like receptor 4/nuclear factor kappaB signaling pathway, down-regulation of NLRP3 in ammasome [8,[24][25][26], which has been proved to be very important for IgA nephropathy in a previous study by our team [27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, NLRP3 are the key in the inflammatory process caused by silica: they are involved, in association with alveolar macrophages, in binding and eliminating crystalline silica particles, and thus leading to pulmonary fibrosis in recent studies. 3,14 The real mechanism and pathophysiology are still not fully elucidated and needs more study to further understand how silica leads to autoimmunity and glomerulonephritis. In our case, simultaneous kidney and pulmonary disease could suggest the hypothesis that Ig A nephropathy might be associated with silica exposure.…”
Section: Discussionmentioning
confidence: 99%